A high performance thermal noise-canceling transimpedance-based differential amplifier - Wangtaphan, Skawrat; Kasemsuwan, Varakorn (My University, 2009)
This paper presents a design of 1.2 V thermal noise-canceling differential amplifier using 0.13 um CMOS technology. The amplifier employs a CMOS inverter-based transimpedance amplifier, and a noise-canceling circuitry. The thermal noise-canceling circuitry is used to cancel channel thermal noise of the input MOSFET. The simulation result shows the noise figure of 2.32 dB. The gain and bandwidth of the amplifier are 42.14 dB and 2 GHz respectively. The power dissipation is 13 mW. ©2009 IEEE.
Keywords: CMOS inverter; Differential amplifier; Noise-canceling; Thermal noise; Transimpedance amplifier